If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(x + 3) = 0 Reorder the terms: 2x + -1(3 + x) = 0 2x + (3 * -1 + x * -1) = 0 2x + (-3 + -1x) = 0 Reorder the terms: -3 + 2x + -1x = 0 Combine like terms: 2x + -1x = 1x -3 + 1x = 0 Solving -3 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 0 + 3 1x = 0 + 3 Combine like terms: 0 + 3 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 30+2x=27+4x | | f(x) = 36x+25 | | 9x-6(3-4x)=-51 | | -5x+(-2.5+-0.375x)=19 | | 2x+6y-4x+7x= | | 7x+1 = +6x+5 | | 4(x+3)=3(2x-4) | | 1=-3+2(2x-2) | | -8y=20+3x | | 6-(-2+5y)= | | -5=8m+12 | | 0.5x+3=0.66666666666x+1 | | 0=200x-400x-300x+400x-500000-444444+27264234 | | 2n+18=4n | | 6-(-a)= | | 4x-3(2x-5)= | | 46-3x=10-9x | | 6x+7=-47-3x | | 7x-12=6x+6 | | 9+4=141 | | 3a-(a-b)= | | -4x-3+(-3x-4)=28 | | 2a-(a+b)= | | isk-3k=6k+5-8k | | 8y-(6y-3)= | | 4x^3+3x^2+3x-1=0 | | 6x+5(20-2x)=12 | | y=lg(x^2-7x+10) | | 3+(-1)*b= | | 0=18000x-450x-5000x-400000-500000 | | x^2-13x+10=0 | | 4x-2xy=7 |